Market cultures : society and morality in the new Asian capitalisms - Hefner, Robert W. (St Leonards, N.S.W. : Allen and Unwin, 1998)
Chinese capitalisms and cultural pluralism. Indigenes and Chinese in Southeast Asia. Southeast Asian capitalisms.
Keywords: Capitalism; East Asia; Southeastern; Capitalism -- East Asia; Capitalism -- Asia, Southeastern; Capitalism -- China; National characteristics; East Asia -- Economic conditions; East Asia -- Social life and customs; Asia, South; China -- Economic conditions; Asia, Southeastern -- Economic conditions